Mapping geosites as gateways to the geotourism management in Central High-Atlas (Morocco) - Bouzekraoui, Hicham; Barakat, Ahmed; El Youssi, Mohammed; Touhami, Fatima; Mouaddine, Atika; Hafid, Abdellatif; Zwoliński, Zbigniew (Quaestiones Geographicae, 2019)
Demnate commune and High-Tessaout valley are located in the Moroccan central High-Atlas. They have a great and much diversified geological and geomorphological heritage and exceptional landscapes of high mountains. The data obtained from the current work indicate that the studied area present high tourist vocation, in the fact that this territory preserves a large number of geosites linked to many witnesses fossils of extinct animals such dinosaurs footprints, outcropping rock formations of the Precambrian and Mesozoic. Further, it has many remarkable landforms and geosites such as canyons, natural bridge, spectacular waterfalls and scree slopes. The findings support that the area attracts many tourists every year. However, this number remains restricted due to the lack of tools of promotion and mediation of its geoheritage and also due to the low exploitation of the geodiversity. Regarding this situation, geotouristic routes represented on touristic map appear as an essential tool for geotourism promotion and as an efficient means of geosciences popularisation. This paper illustrates three geotouristic routes describing the main geosites in rural areas of Demnate and High-Tessaout valley. These geotourism itineraries can help to explain the high potential interest of the studied areas in geotourism terms.